Fundamentals of anatomy & physiology - Rizzo, Donald C. (Clifton Park, NY : Delmar, Cengage Learning, 2010)
A text designed for learners in the allied health field with little or no prior biology or anatomy and physiology knowledge.--
The human body -- The chemistry of life -- Cell structure -- Cellular metabolism and reproduction: mitosis and meiosis -- Tissues -- The integumentary system -- The skeletal system -- The articular system -- The muscular system -- The nervous system: introduction, spinal cord, and spinal nerves -- The nervous system: the brain, cranial nerves, autonomic nervous system, and the special senses -- The endocrine system -- The blood -- The cardiovascular system -- The lymphatic system -- Nutrition and the digestive system -- The respiratory system -- The urinary system -- The reproductive system.
Book is accompanied by one cd-rom bearing the same call number and available at Makmal Perpustakaan Pra Klinikal.
Title on disc surface: StudyWare to accompany Fundamentals of anatomy & physiology.
System requirements for accompanying CD-ROM: Windows XP operating system, or Windows Vista; 225 MB hard drive space; Adobe flash player 9.
Keywords: Anatomy; Physiology